Kv1.3 Ion Channels Mediate Electrical Stimulation-Induced Collagen Expression in Human Dermal Fibroblasts - Catherine Obiajulu; Diem Nguyen; Kim Hoang Ngan Bui; Timothy Tran; Annamarie Vu; Cortney Ngo; Ian A. Slowinski; Kazuyuki Miyazawa; Katarzyna Slowinska (Cosmetics, 2025)
Electrical stimulation of the skin has proven effective in pain management and antibacterial treatment, particularly in wound healing and counteracting the aging processes. The latter processes rely on epidermal cell migration, increased fibroblast proliferation, and upregulation of extracellular matrix protein expression. While an electrical field stimulates these processes, it is unclear how the electrical signal results in transcriptional control. Here, we postulate that the activation of voltage-gated channels, specifically voltage-gated potassium channels Kv1.3, is implicated in initiating the downstream signaling pathways that lead to increased collagen expression. We postulate that Kv1.3 and possibly calcium-activated potassium channel activity leads to the engagement of store-operated calcium channels and modulates the intracellular calcium ions distribution. In turn, changes in intracellular calcium concentration can activate calcium-generated transcriptional effectors. The Kv1.3 channel, identified via fluorescence imaging with ShK toxin (peptide), shows high-level expression in the human dermal fibroblast cell membrane. We also performed proliferation, collagen expression, and calcium imaging studies for variable electrical fields to help understand the link between the electrical stimulation, Kv1.3 channels, intracellular calcium concentration, and protein expression.